5t=-4+6t

Simple and best practice solution for 5t=-4+6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t=-4+6t equation:



5t=-4+6t
We move all terms to the left:
5t-(-4+6t)=0
We add all the numbers together, and all the variables
5t-(6t-4)=0
We get rid of parentheses
5t-6t+4=0
We add all the numbers together, and all the variables
-1t+4=0
We move all terms containing t to the left, all other terms to the right
-t=-4
t=-4/-1
t=+4

See similar equations:

| 10q+3q+5=2q(q-3) | | m-3=-20 | | -5u−-13u+-12u+-10=-18 | | 4^(x^2-1)-2=0 | | 5(-7+4x)=25 | | s/9=9 | | 2(r-6)-5=-1 | | S^2-11s+36=s | | 1+1+1/6x=13 | | c=1000 | | (3x+8)–(2x+7)x=3 | | 0.2x+0.7x=7 | | -3h=-4h-6 | | 3t-2t+3=9 | | (8x+3)+6=11 | | 2x+4=6x+I | | -4-7s=-8s | | 5w+28=36 | | 66=6b | | 3x-12=7x+8= | | |7-2x^2|=11 | | 2(-3x-5)=-10 | | 13-m=6 | | x^2-13x+27=0 | | 5x(3+1)+3=13 | | 3.9=5.3-0.7x | | 28-7x=-7(x-4) | | 8-3y/5y-3=2/3 | | -4=16f | | 8x-5x+9=-6 | | 9w-13w=-24 | | 12x-3x=72 |

Equations solver categories